Sports potential modeling of young basketball players: a preliminary analysis - Ribeiro Junior, D. B.; Vianna, J. M.; Lauria, A. A.; Coelho, E. F.; Werneck, F. Z. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2019)
The aims of this study were: 1) to evaluate the sports potential of young basketball players; 2) to identify variables that discriminate sports potential assessed by coaches; 3) to verify the relationship between classification of the multidimensional profile of athletes and classification of the sports potential by coaches. Sixty-two young basketball players aged 15.6±1.1 years from U-15 (n = 24) and U-17 (n = 38) categories participated in the study. A test battery was applied to evaluate sports potential indicators: 1) anthropometric; 2) physicomotor; 3) psychological; 4) skills; 5) socio-environmental; 6) maturational and 7) sports potential. Cluster analysis was performed in three groups: high, medium and low potential. Student`s t-test was used for the comparison between athletes evaluated by the coach as excellent and the others and the Chi-Square test to verify the relationship between sports potential classifications. It was observed that in the high-potential group, athletes were chronologically older, with higher % predicted adult height (PMS), competitive and determined sports orientation, higher body size, lower skinfold summation, and greater physicomotor performance. In comparison with other athletes, high-potential basketball players presented higher stature, wider wingspan, longer limb length, greater predicted adult stature and higher Z score of the % PMS. It could be concluded that the multidimensional approach was useful for the evaluation of the sports potential of young basketball players, requiring the use of multidimensional variables, in addition to coaches` opinion regarding the potential of their athletes.